Building sustainable performance in the maritime industry via digital resources and innovation - Chua, Celine (2024)
Given the growing limelight on digital revolution and sustainability in the maritime industry, this paper aims to investigate the overlaps and interconnectedness of these two significant topics. Anchored on resource-based view and organisational ambidexterity theories, this study investigates the influence of key technical and social digital resources on exploratory and exploitative innovation capabilities and sustainable performance of maritime companies. This study also analyses the direct effects of innovation constructs and the indirect effects of digital resources on sustainable performance. Survey data were collected from 164 maritime professionals from various functions and sectors in the maritime industry. The structural equation modelling analysis revealed that all identified digital resources have a significant, positive correlation with innovation constructs, as well as a positive indirect effect on sustainable performance. Furthermore, as compared to exploitative innovation, exploratory innovation generates a greater positive effect on sustainable performance. This study enriches theoretical research by enhancing the understanding of resource-based view and organisational ambidexterity. It also explores the tensions between exploratory and exploitative innovation, as well as the definition of sustainable performance. It offers managerial implications by recommending how the management can utilise technical and social digital resources and innovation to improve sustainable performance via better long-term planning and corporate decisions. In addition, this study also enables firms to prioritise their allocation of resources where finances or manpower are scarce.